Cotton in the Mexicali Valley, Mexico and the Limits of State Interventionism (1914-1950) - Almaraz, Araceli (2015)
The first cotton boom in the Mexicali Valley in northeastern Mexico took place during the first half of the 20th century and was facilitated by United States investors. Cotton production reached its highest levels starting in 1920-1930 and continued into the 1960s. In this area, which does not have a history of colonial haciendas, about 20 United States companies initiated and developed this agricultural enterprise, following an export strategy. The central hypothesis of this study is that the presence of United States firms, which established the agricultural structure of this area through control of land, water, and labor, could not be immediately substituted by Mexican government institutions that sought to position themselves as central actors in the regional economy.